Analisis Semiotika Makna Denotasi dan Konotasi dalam Syi’ir Al-I’tiraf Karya Abu Nawas Berdasarkan Teori Roland Barthes - Rika Indri Cahyani; Akmaliyah (Mauriduna : Journal of Islamic Studies, 2025)
This study aims to analyze the denotative and connotative meanings in the poem Al-I'tiraf by Abu Nawas based on Roland Barthes' semiotic theory. The research employs a qualitative method, with data collection techniques including observation and documentation. The data analysis utilizes Barthes' semiotic approach to identify denotative and connotative signs present in the poem. Denotative meaning reflects the direct meaning of the words, while connotative meaning encompasses deeper layers of meaning, illustrating a universal inner experience of faith, expressing regret, fear, humility, complete dependence, hope, and trust in Allah's mercy. The findings indicate that Al-I'tiraf is not merely an aesthetic literary work but also a medium of communication rich in social messages and philosophical reflection. This study provides new insights into understanding Arabic literary works through the lens of modern semiotics and enriches literary studies by employing Barthes' semiotic theory as an analytical tool.